Stainless Steel: Material Facts for the Orthodontic Practitioner (2015)
Abstract. Stainless steel is one of the most widely used materials in current orthodontics.Archwires, brackets, bands, ligatures, tubes, among other appliances, aremanufactured using different types of this alloy. The first evidence of the use ofthis alloy in the orthodontic field dates back to the mid-1920s, when it was introducedas a material to manufacture wires. The alloy has ever since gained popularityamong orthodontists and its further development has led to its widespread usein today’s different orthodontic techniques. Despite being available for more than80 years, and the fact that most orthodontists use it on a daily basis, there is still alack of knowledge about the basic principles, composition, and properties of thismaterial by these professionals. Therefore, the purpose of this literature review isto discuss the main characteristics and properties of stainless steel that are usefulin the orthodontic practice for orthodontists to take advantage of this remarkablematerial.